The Discourse of Globalization: Framing and Sensemaking of an Emerging Concept - Fiss, Peer C.; Hirsch, Paul M. (American Sociological Review, 2005)
While the literature on framing has importantly expanded our understanding of frame creation and contests from an interpretive point of view, previous studies have largely neglected the structural contexts in which framing activities occur. In this study, we propose extending the framing approach by incorporating insights from the literature on sensemaking to examine how and when opportunities for meaning creation open up and how this affects subsequent discursive processes. Connecting framing and sensemaking better enables us to examine how structural factors prompt and bound discursive processes, affecting when and where frame contests emerge. We demonstrate the utility of this approach by examining changes in the discourse of globalization. Using qualitative and quantitative analyses of newspaper articles and corporate press releases, we trace the emergence of globalization discourse, its diffusion, and the increasing contention that surrounds it. Our findings show how and where globalization discourse emerged in response to greater U.S. involvement with the international economy, and how later frame contests over the meaning of globalization have depended on the interests of the actors involved.